Comparison of the performance and safety of 2 ophthalmic viscosurgical devices in cataract surgery. Issue 3 (January 2017) - Auffarth, Gerd U.; Auerbach, Florian N.; Rabsilber, Tanja; Gegúndez, José A.; Cuiña, Ricardo; Renard, Yves; Vinciguerra, Paolo; Camesasca, Fabrizio; Van Cauwenberge, Francoise; Amzallag, Thierry; Van Setten, Gysbert; Holzer, Mike P.
Abstract : Purpose : To compare the clinical performance and safety of 2 ophthalmic viscosurgical devices (OVDs)—Twinvisc (OVD 1) and Duovisc (OVD 2)—in cataract surgery. Setting : European multicenter study. Design : Prospective randomized controlled study. Methods : Patients with cataract had phacoemulsification and intraocular lens implantation in 1 eye. They were randomly assigned to receive OVD 1 or OVD 2. Preoperative and postoperative examinations over 3 months included mean intraocular pressure (IOP), incidence of IOP peaks (≥30 mm Hg and ≥24 mm Hg), endothelial cell count (ECC), corneal thickness, and intraocular inflammation. A subjective evaluation of the OVDs was performed. Results : The study comprised 220 patients. The incidence of IOP peaks and the mean IOP were not statistically significantly different between the 2 groups at any of the follow‐up visits. At 6 hours, the incidence of IOP spikes 30 mm Hg or higher was 6.5% and 7.2% in the OVD 1 and the OVD 2 groups, respectively ( P = .846). For the IOP spikes 24 mm Hg or higher, the incidence was 16.8% and 25.2%, respectively ( P = .128). Three months postoperatively there was no statistically significant difference in ECC and pachymetry between the 2 groups. Mild inflammation was noticed up to 7 days postoperatively after which it resolved in both groups. Subjectively, the OVD 2 was easier to use, whereas the OVD 1 had better cohesive and dispersive properties. Conclusions : Both OVDs have similar performance and safety profiles in phacoemulsification cataract surgery. No clinically relevant differences were found between the 2 devices regarding transient IOP spikes, mean IOP, corneal endothelium injury, or inflammation.